Preferences of Indian Meal Moth Larvae for Different Dog Foods - Schmidt, Tanner; Aikins, M. Jamie; Phillips, Thomas W. (My University, 2018)
Indian meal moths (IMM), Plodiainterpuntella, are persistent pests to our foods (Fasulo et al.1998; Plunkett’s Pest Control 2018). When IMMs infest a a food product the resulting value loss is the result of contamination by larvae that leave droppings and silken webs in grain and grain products (Jacob and Calvin 2001). The IMM is an important pest of high-value dog foods and the grain components of these food may influence their infestation. Experiments were conducted with eggs of the IMM to determine if moth larvae would choose and infest the grain-based dog food in comparison to dog foods with a higher meat content. IMM laboratory rearing diet was included for comparison. No-choice and choice tests confirmed the IMM diet to be the most preferred and best for larval development. Forced infestation of 50 IMM eggs on the four different dog foods found difference among them. In two-choice test that require newly hatched larvae to walk to and infest either lab diet or a dog food, the highest proportion of larvae selecting any of the dog foods was on product C, which was a medium quality, grain-free food. These results suggest that IMM infestations in warehouses or consumer’s homes could be prevalent on some dog foods more than others.
Keywords: Fall 2018